Medidas radiográficas y corporales para diagnosticar relaciones de clase II utilizando análisis estadístico multivariado - Rincón-R., Ramiro; Restrepo-R., Ligia Isabel; Agudelo-G., Yakeline; Echeverri-V., Juan David (Revista Facultad de Odontología Universidad de Antioquia, 2015)
More than 40 variables are used in the process of orthodontic diagnosis and each one of them depends on every individual author. Of these variables only some contribute sufficient information to carry out a diagnosis of class II. When so many variables are available it is necessary to use a method that allows to identify the representative variables and to eliminate those that are redundant. To obtain this objective, a multiway analysis of variance was used (Main Components Analysis, Factor Analysis, Cluster Analysis and Discriminate Analysis), which identifies the variables of Angle of Lande, the Angle of Convexity and the distance from the point A to the perpendicular of FH, the subgroups and the factors were identified (constructed) by gender and lastly the Discriminate Function was obtained to identify the Class II malocclusion. With the Multiway Analysis of variance it was possible to reduce the number of variables used for the diagnostic process.